Collective memory of modern Dagestanis about the local heroes of the Russian civil war : Heroic narratives and ethnic identity - Grigoryev, Grigory (Helsingin yliopisto, 2024)
Although roughly the size of Scotland, the republic of Dagestan, which is situated in the Russian North Caucasus region is a home to at least 32 distinct ethnic groups. These groups live in a constant competition for scarce land, economic and symbolic resources. The legal practices in Dagestan are split between Sharia, Russian law and adat (customary law), while the religious landscape is contested by the Sufi, Salafi and various other “new” and “traditional” Muslim communities. Conquered and annexed by the Russian Empire in mid XIX century, Dagestan with all its uniqueness and distinctiveness, can also be described as the most “Russian” region when it comes to social maladies – it suffers from extreme levels of corruption, unemployment, poverty and state violence. The data for this research project was collected over four summers of fieldwork (2016–2020), during which I visited and lived in seven Dagestani villages and the city of Makhachkala. My methodology is based on oral history studies, narratology and thematic analysis. The collective memory studies tradition acts as the central theoretical foundation of my dissertation. It allows me to focus on the relations between the representations of the past and the collective identities of the groups engaged in creating such representations. Following the above-mentioned theoretical and methodological perspectives I formulated two research questions: what is a) the structure and b) function of oral historical narratives of modern Dagestani communities. Through the analysis of the narratives’ structure and functions I have managed to establish my hypothesis which is that the representations of the past circulating in Dagestani communities a) carry information about their current social dynamics (group boundaries, identities, conflicts) and b) are employed by the communities as a limited and energetically applied resource, invaluable in the ethnic, religious and political competition. I focus on five Dagestani village communities, which belong to three ethnic ...